2024
DOI: 10.1021/acs.joc.3c01750
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Formal [2 + 2]-Retrocyclization of Cyclobutanols via 2-Fold Csp3–Csp3 Bond Cleavage

Sergio Parra-García,
Marina Ballester-Ibáñez,
José-Antonio García-López

Abstract: In this work, we describe the unexpected 2-fold Csp 3 −Csp 3 bond cleavage suffered by cyclobutanols in the presence of a catalytic amount of Pd(OAc) 2 and promoted by the bulky biaryl JohnPhos ligand. Overall, the sequential cleavage of a strained and an unstrained Csp 3 −Csp 3 bond leads to the formal [2 + 2]-retrocyclization products, namely, styrene and acetophenone derivatives. This procedure might enable the use of cyclobutanols as masked acetyl groups, resisting harsh conditions in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, a minor polymeric series showed a mass corresponding to a Me­(CO)-C 6 H 4 end-group (Scheme f). We have previously observed that cyclobutanol reagents can undergo a Pd-catalyzed 2-fold C­(sp 3 )–C­(sp 3 ) bond cleavage, especially when using JohnPhos as a ligand . This process provokes the formal [2 + 2]-retrocyclization of the cyclobutanol fragment, giving the corresponding alkene and acetophenone.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a minor polymeric series showed a mass corresponding to a Me­(CO)-C 6 H 4 end-group (Scheme f). We have previously observed that cyclobutanol reagents can undergo a Pd-catalyzed 2-fold C­(sp 3 )–C­(sp 3 ) bond cleavage, especially when using JohnPhos as a ligand . This process provokes the formal [2 + 2]-retrocyclization of the cyclobutanol fragment, giving the corresponding alkene and acetophenone.…”
Section: Resultsmentioning
confidence: 99%